Transient receptor potential vanilloid subtype 1 depletion mediates mechanical allodynia through cellular signal alterations in small-fiber neuropathy. (2nd April 2021) - Chang, Chin-Hong; Chang, Ying-Shuang; Hsieh, Yu-Lin
Abstract : TRPV1, a polymodal nociceptor, depletion not only leads to thermal analgesia, but also develops mechanical allodynia through the alteration of cellular analgesia and signal in small-fiber neuropathy. Abstract: Transient receptor potential vanilloid subtype 1 (TRPV1) is a polymodal nociceptor that monitors noxious thermal sensations. Few studies have addressed the role of TRPV1 in mechanical allodynia in small-fiber neuropathy (SFN) caused by sensory nerve damage. Accordingly, this article reviews the putative mechanisms of TRPV1 depletion that mediates mechanical allodynia in SFN. The intraepidermal nerve fibers (IENFs) degeneration and sensory neuronal injury are the primary characteristics of SFN. Intraepidermal nerve fibers are mainly C-polymodal nociceptors and Aδ-fibers, which mediated allodynic pain after neuronal sensitization. TRPV1 depletion by highly potent neurotoxins induces the upregulation of activating transcription factor 3 and IENFs degeneration which mimics SFN. TRPV1 is predominately expressed by the peptidergic than nonpeptidergic nociceptors, and these neurochemical discrepancies provided the basis of the distinct pathways of thermal analgesia and mechanical allodynia. The depletion of peptidergic nociceptors and their IENFs cause thermal analgesia and sensitized nonpeptidergic nociceptors respond to mechanical allodynia. These distinct pathways of noxious stimuli suggested determined by the neurochemical-dependent neurotrophin cognate receptors such as TrkA and Ret receptors. The neurogenic inflammation after TRPV1 depletion also sensitized Ret receptors which results in mechanical allodynia. The activation of spinal TRPV1(+) neurons may contribute to mechanical allodynia. Also, an imbalance in adenosinergic analgesic signaling in sensory neurons such as the downregulation of prostatic acid phosphatase and adenosine A1 receptors, which colocalized with TRPV1 as a membrane microdomain also correlated with the development of mechanical allodynia. Collectively, TRPV1 depletion–induced mechanical allodynia involves a complicated cascade of cellular signaling alterations.